Leukocyte count, systemic inflammation, and health status in older adults: a narrative review - Chmielewski, Piotr (Anthropological Review, 2018)
Epidemiological and clinical studies suggest that elevated leukocyte count within the normal range can predict cardiovascular and total mortality in older adults. These findings are remarkable because this simple and common laboratory test is included in routine medical check-ups. It is well known that chronic systemic inflammation (inflammaging) is one of the hallmarks of aging and an important component of obesity-associated insulin resistance that can lead to type 2 diabetes and other health problems in both overweight individuals and elderly people. To understand the molecular mechanisms linking increased systemic inflammation with aging-associated diseases and elevated leukocyte counts in the elderly is to unravel the multiplicity of molecular factors and mechanisms involved in chronic low-grade systemic inflammation, the gradual accumulation of random molecular damage, age-related diseases, and the process of leukopoiesis. There are several possible mechanisms through which chronic low-grade systemic inflammation is associated with both higher leukocyte count and a greater risk of aging-associated conditions in older adults. For example, the IL-6 centric model predicts that this biomediator is involved in chronic systemic inflammation and leukopoiesis, thereby suggesting that elevated leukocyte count is a signal of poor health in older adults. Alternatively, an increase in neutrophil and monocyte counts can be a direct cause of cardiovascular events in the elderly. Interestingly, some authors assert that the predictive ability of elevated leukocyte counts with regard to cardiovascular and allcause mortality among older adults surpass the predictive value of total cholesterol. This review reports the recent findings on the links between elevated but normal leukocyte counts and the increased risks of all-cause, cardiovascular, and cancer mortality. The possible molecular mechanisms linking higher but normal leukocyte counts with increased risk of aging-associated diseases in the elderly are discussed here.